Impact of mineral dust photochemistry on the atmosphere - DUPART, YOAN (HAL CCSD, 2012)
The objective of this work is to study the heterogeneous processes of mineral dust surfacesunder UV-A radiation. It is know that mineral dust containing metal oxides which can absorbsolar radiation and therefore activate a different chemistry compared to that observed in thedark. In order to avoid measurement artifacts related to the nature of macroscopic films, anaerosol flow tube was developed during this work and applied to study the interactions ofSO2, NO2 and O3 with real mineral dust.An unexpected formation of new particles in the presence of SO2 was observed. In order toexplain this phenomenon, we suggest the desorption of OH radicals from the mineral dustsurface to the gas phase. This mechanism has also been supported by field campaigns.Using real samples of volcanic ash from the last eruption of Eyjafjallajökull in Iceland (2010)allowed us study capture of SO2 on macroscopic ashes films with uptake coefficient around10-7. Associated kinetic experiments combined with chemical analysis allowed us to propose areaction mechanism explaining the formation of iron sulfate on the surface of ashes.Finally, we investigated the photochemical interactions of O3 and NO2 with minerals dustaerosols in the flow tube reactor showing a good agreement with previous data obtained onmacroscopic surfaces. Les travaux de cette thèse reposent sur l’étude des processus hétérogènes à la surface desparticules minérales en présence d’irradiation UV-A. Nous savons que les poussièresminérales contiennent des oxydes métalliques pouvant absorber la radiation solaire et ainsiactiver une chimie très différente de celle observée à l’obscurité. Un réacteur à écoulementd’aérosols a été utilisé pour étudier les interactions des gaz (SO2, NO2 et O3) avec devéritables poussières minérales, évitant ainsi les artéfacts de mesure liés à la naturemacroscopique des films comme dans les études précédentes.La mise en suspension des poussières minérales a permis d’observer une formation inattenduede nouvelles particules ultrafines en présence de ...